Picture archiving and communication systems in the South African public healthcare environment : a suitable structure and guidelines to assist implementation and optimisation - Triegaardt, Myra (Stellenbosch : Stellenbosch University, 2013)
Thesis (MScEng)-- Stellenbosch University, 2013.